Analisis Kebutuhan Layanan Bimbingan Klasikal Joyful Podcast untuk Meningkatkan Kepercayaan Diri Siswa SMP - Kartiningsih, Rina; Suriswo, Suriswo; Nugroho, Rahmad Agung (Jurnal Simki Pedagogia, 2026)
The objective of this research is to explore the necessity for designing a classical guidance model utilizing the joyful podcast method to foster self-confidence among junior high school students. This study was conducted using a research and development approach, with emphasis placed on the preliminary stage of needs analysis. The research population included seventh-grade students, guidance counselors, and homeroom teachers at a state junior high school in Brebes, and the sample was selected through purposive sampling. Data collection techniques comprised questionnaires and interviews, while the analysis was carried out using descriptive qualitative and quantitative methods. The findings indicated that students often struggle with low self-confidence in both academic and interpersonal contexts, and the existing classical guidance services tend to be seen as unvaried and less stimulating. Respondents generally welcomed the idea of integrating more enjoyable and media-rich tools into the guidance process. These insights support the appropriateness of the joyful podcast as a medium for enhancing the effectiveness of classical guidance sessions. It was concluded that developing a guidance model incorporating the joyful podcast approach is both relevant and potentially beneficial in improving student self-confidence.